PENGARUH PERILAKU DOSEN DALAM MENGAJAR TERHADAP MINAT BELAJAR MAHASISWA JURUSAN ADMINISTRASI BISNIS - Esya Alhadi; Rini Rini; Yusleli Herawati (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2013)
The objective of the research is to find out whether or not the lecturer attitude of Business Administration Majaority in teaching could influence the learning of college student?  The data were collected with questionnaire and the analyzing of the data was helped by SPSS version 12.00 program.  The results have shown that three of independent variables of lecturer which consist of teaching method, lecturer ethics in teaching and the lecturer obedience in regulation simultaneously and partially influenced toward the learning as the dependent variable.  The number of the influence was 49,10% and the rest was influenced by the other variables.  The most dominant factor that was influential on the learning interest of college student was the lecturer etchics in teaching.  To give more improvement toward the learning interest of college student at Business Administration Majority, it was recommended to Business Administration Majority’s lecturer to be more ready in teaching, starting from the teaching method such as preparing the tuition contract, SAP, teaching material, etc.  The lecturer ethics in the class also should be kept, for example the attitude in communicating to the college student, likewise with the regulation obedience, it is better for the lecturer to always obey the teaching time, giving score transparency, etc. Thus, besides improving the learning interest of college student, the lecturer could be the good role model to the college student.